Ability of fabric face mask materials to filter ultrafine particles at coughing velocity - James Ward; P John Clarkson; Eugenia O'Kelly; Sophia Pirog (BMJ Open)
Objective We examined the ability of fabrics which might be used to create home-made face masks to filter out ultrafine (0.02–0.1 µm) particles at the velocity of adult human coughing.Methods Twenty commonly available fabrics and materials were evaluated for their ability to reduce air concentrations of ultrafine particles at coughing face velocities. Further assessment was made on the filtration ability of selected fabrics while damp and of fabric combinations which might be used to construct home-made masks.Results Single fabric layers blocked a range of ultrafine particles. When fabrics were layered, a higher percentage of ultrafine particles were filtered. The average filtration efficiency of single layer fabrics and of layered combination was found to be 35% and 45%, respectively. Non-woven fusible interfacing, when combined with other fabrics, could add up to 11% additional filtration efficiency. However, fabric and fabric combinations were more difficult to breathe through than N95 masks.Conclusions The current coronavirus pandemic has left many communities without access to N95 face masks. Our findings suggest that face masks made from layered common fabric can help filter ultrafine particles and provide some protection for the wearer when commercial face masks are unavailable.